2007
DOI: 10.1128/aem.01570-06
|View full text |Cite
|
Sign up to set email alerts
|

Communities of Archaea and Bacteria in a Subsurface Radioactive Thermal Spring in the Austrian Central Alps, and Evidence of Ammonia-Oxidizing Crenarchaeota

Abstract: Scanning electron microscopy revealed great morphological diversity in biofilms from several largely unexplored subterranean thermal Alpine springs, which contain radium 226 and radon 222. A culture-independent molecular analysis of microbial communities on rocks and in the water of one spring, the "Franz-Josef-Quelle" in Bad Gastein, Austria, was performed. Four hundred fifteen clones were analyzed. One hundred thirty-two sequences were affiliated with 14 bacterial operational taxonomic units (OTUs) and 283 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
112
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(126 citation statements)
references
References 47 publications
12
112
0
2
Order By: Relevance
“…As only one archaeal 16S rRNA phylotype (by using a threshold of 97% sequence similarity) was found in the enrichment, the retrieved archaeal amoA and amoB gene fragments most likely also originated from this phylotype. In contrast to previous studies, which only reported the presence of AOA-related 16S rRNA or crenarchaeotal amoA gene fragments in thermophilic environments (19,20,(31)(32)(33), we specifically identified the respective organism by CARD-FISH with 16S rRNA-targeted probes as cocci in irregularly shaped aggregates. Furthermore, we propose three independent lines of evidence that, taken together, strongly suggest that the detected archaeon is actually an AOA.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…As only one archaeal 16S rRNA phylotype (by using a threshold of 97% sequence similarity) was found in the enrichment, the retrieved archaeal amoA and amoB gene fragments most likely also originated from this phylotype. In contrast to previous studies, which only reported the presence of AOA-related 16S rRNA or crenarchaeotal amoA gene fragments in thermophilic environments (19,20,(31)(32)(33), we specifically identified the respective organism by CARD-FISH with 16S rRNA-targeted probes as cocci in irregularly shaped aggregates. Furthermore, we propose three independent lines of evidence that, taken together, strongly suggest that the detected archaeon is actually an AOA.…”
Section: Discussionmentioning
confidence: 56%
“…All 46 sequences were related at Ͼ99.1% similarity to each other and assigned to a monophyletic cluster within Crenarchaeota group I.1b (soil group; Fig. 1) that also included partial 16S rRNA gene sequences recently retrieved from a subsurface radioactive thermal spring (20) and a Wisconsin soil (28). In addition, crenarchaeotal amo genes were PCR-amplified from the enrichment, and 19 and 7 clones were sequenced for amoA and amoB, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study showed that the fumaroles themselves are likely dominated by endemic taxa, including deep-branching Planctomycetes, Acidobacteria and Chloroflexi, as well as many novel, potentially division-level lineages with no known relatives 17 . The few Archaea observed at Tramway Ridge were all classified as Crenarchaeota and were most similar to environmental clones from subsurface environments in South Africa 19 and central Europe 20 .…”
mentioning
confidence: 98%
“…Desde a sua descoberta, muitos trabalhos vêm relatando a presença de AOAs em diversos ambientes, como solos (Ying et al, 2010;Gubry-Rangin et al, 2011;Zhang et al, 2010), água marinha (Könneke et al, 2005;Wuchter et al, 2006), sedimentos marinhos (Francis et al, 2005;Beman & Francis, 2006), aquários e fontes de água doce (Sauder et al, 2011;Peng et al, 2013), biorreatores de tratamento de esgoto (Park et al, 2006), fontes termais (Weidler et al, 2007), entre outros. Além disso, a predominância de AOAs em relação às AOBs em certos ambientes também vem sendo sugerida, principalmente em alguns solos (Leininger et al, 2006;Nicol et al, 2008).…”
Section: Archaeas Oxidantes De Amônia (Aoas)unclassified